The Hazard Analysis System and Critical Control Points as a quality tool in brazilian food industry - Martins, Alexsandra Alves Bezerra; Universidade Federal do Ceará (2019)
Food safety is one of the main problems related to food production and processing. The control of food contamination hazards in relation to physical, chemical and biological risks must occur during all phases of the production process, that is, from the acquisition of the raw material to the production of the final product that arrives at the consumer's table. Food industries need an effective quality system to exercise quality control at all stages of production. The Hazard Analysis and Critical Control Points (HACCP) system stands out today as the most important quality control system in the food industry, capable of identifying the likely risks of contamination within a specific process and the measures preventive measures to control them, aiming at food safety.